Effect of UNOS policy change and exception status request on outcomes in patients bridged to heart transplant with an intra‐aortic balloon pump. Issue 5 (17th November 2021) - Wolfson, Aaron M.; DePasquale, Eugene C.; Starnes, Vaughn A.; Cunningham, Mark; Baker, Craig; Lee, Raymond; Bowdish, Michael; Fong, Michael W.; Rahman, Joseph; Pandya, Kruti; Lewinger, Juan Pablo; Kawaguchi, Eric S.; et al.
Abstract: Background: Intra‐aortic balloon pumps (IABP) are used to bridge select end‐stage heart disease patients to heart transplant (HT). IABP use and exception requests both increased dramatically after the UNOS policy change (PC). The purpose of this study was to evaluate the effect of PC and exception status requests on waitlist and post‐transplant outcomes in patients bridged to HT with IABP support. Methods: We analyzed adult, first‐time, single‐organ HT recipients from the UNOS Registry either on IABP at the time of registration for HT or at the time of HT. We compared waitlist and post‐HT outcomes between patients from the PRE (October 18, 2016 to May 30, 2018) and POST (October 18, 2018 to May 30, 2020) eras using Kaplan‐Meier curves and time‐to‐event analyses. Results: A total of 1267 patients underwent HT from IABP (261 pre‐policy/1006 post‐policy). On multivariate analysis, PC was associated with an increase in HT (sub‐distribution hazard ratio (sdHR): 2.15, p  < .001) and decrease in death/deterioration (sdHR: 0.55, p  = .011) on the waitlist with no effect on 1‐year post‐HT survival ( p  = .8). The exception status of patients undergoing HT was predominantly seen in the POST era (29%, 293/1006); only four patients in the PRE era. Exception requests in the POST era did not alter patient outcomes. Conclusions: In patients bridged to heart transplant with an IABP, policy change is associated with decreased rates of death/deterioration and increased rates of heart transplantation on the waitlist without affecting 1‐year post‐transplant survival. While exception status use has markedly increased post‐PC, it is not associated with patient outcomes. Abstract : Cumulative incidence curves (waitlist outcomes) are shown in the two left columns and Kaplan‐Meier Curves (post‐transplant survival) are in the right two columns. The top row compares outcomes based on policy change era and the bottom row compares outcomes based on exception status; p ‐values are shown on the figure.